ANALISIS PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MULTIMEDIA INTERAKTIF DI KELAS V SDN 4 PANDANWANGI - Maya Sofia Azizah; ST.Nurul Fitriani,S.Pd.,M.Si; Marudin,M.Pd.I (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the enhancement of student learning outcomes through the implementation of interactive multimedia in the fifth-grade Civics Education (PPKn) class at SDN 4 Pandanwangi. The research problem stems from the conventional teaching methods, primarily lectures and textbooks, which result in low student engagement and difficulty in understanding abstract concepts such as legal norms and Pancasila values. The objective is to examine how interactive multimedia impacts students’ learning outcomes in PPKn. A qualitative research method was employed, utilizing observation, interviews, and written tests to collect data from July to September 2025. The interactive multimedia, developed using Microsoft PowerPoint with navigation features, visuals, animations, audio, and interactive quizzes, was designed to be accessible offline, addressing the school’s limited technological infrastructure. The findings indicate that interactive multimedia fosters a more engaging and enjoyable learning environment, enhancing students’ enthusiasm and participation. However, the average student score of 60.25 did not meet the minimum competency standard, suggesting that the method was not fully effective in achieving the desired learning outcomes. Factors supporting its implementation include conducive classroom conditions and teacher creativity, though challenges such as inadequate facilities persist. This study contributes to the theoretical understanding of multimedia in education and offers practical insights for teachers to integrate technology in PPKn lessons, recommending further development of interactive media to enhance educational quality.